SISTEM PERAMALAN JUMLAH PENUMPANG KAPAL LAUT DI PELABUHAN TANJUNG PERAK SURABAYA MENGGUNAKAN TRIPLE EKSPONENSIAL SMOOTHING BERBASIS ANDROID - andini, titania dwi; Sunyoto, Rike Mariska (P3M Politeknik Negeri Banjarmasin, 2018)
Tanjung Perak is the second largest and busiest port in Indonesia after the Tanjung Priok Port and also as a trade center to the eastern part of Indonesia. Tanjung Perak Port is included in the work unit at PT. (Persero) Pelabuhan Indonesia III. Along with the development of the port, passengers who pass the Tanjung Perak port are also increasing. There are frequent spikes during Eid and the end of the year. Porters have difficulty predicting the number of passengers on ships. Based on the pattern of data on the number of ship passengers in 2015-2017, the seasonal pattern of data tends to fluctuate. So in predicting it, amethod is used triple exponential smoothing. This study will produce a forecasting system for the number of ship passengers in the port of Tanjung Perak for several future periods based on Android. Android as one of the operating systems that works on smartphones is a widely used operating system. With the use of Android-based applications, it is expected that the results of forecasting the number of marine vessels can be accessed on a mobile basis so that it is not limited to time and place.